Relevance, Retrieval and Document Spaces - Robertson, Stephen (Proceedings of IRFIS 3, Oslo, 1979, 1979)
It has long been accepted that, in documentary information retrieval, we can seldom expect to find a document or documents that match the initial statement of a query precisely in every detail. Some documents may be found which match the query to a greater or lesser degree, and of these some may turn out to be useful and some not.